2017
DOI: 10.1063/1.4996172
|View full text |Cite
|
Sign up to set email alerts
|

Ohmic contacts on n-type β-Ga2O3 using AZO/Ti/Au

Abstract: AZO interlayers between n-Ga2O3 and Ti/Au metallization significantly enhance Ohmic contact formation after annealing at ≥ 300°C. Without the presence of the AZO, similar anneals produce only rectifying current-voltage characteristics. Transmission Line Measurements of the Au/Ti/AZO/Ga2O3 stacks showed the specific contact resistance and transfer resistance decreased sharply from as-deposited values with annealing. The minimum contact resistance and specific contact resistance of 0.42 Ω-mm and 2.82 × 10-5 Ω-cm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
41
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 56 publications
(41 citation statements)
references
References 34 publications
(52 reference statements)
0
41
0
Order By: Relevance
“…It is always challenging to make low resistance Ohmic contacts to wide bandgap semiconductors and generally some form of local doping enhancement by ion implantation, [12,33,34] plasma exposure, [12] or the addition of a low bandgap interlayer (AZO, ITO, InN) [35,36] is used. Ion implantation is still relatively unexplored in Ga 2 O 3 in terms of choice of species, doses, and annealing conditions.…”
Section: Ohmic Contactsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is always challenging to make low resistance Ohmic contacts to wide bandgap semiconductors and generally some form of local doping enhancement by ion implantation, [12,33,34] plasma exposure, [12] or the addition of a low bandgap interlayer (AZO, ITO, InN) [35,36] is used. Ion implantation is still relatively unexplored in Ga 2 O 3 in terms of choice of species, doses, and annealing conditions.…”
Section: Ohmic Contactsmentioning
confidence: 99%
“…[15] Carey et al reported Al-doped ZnO (AZO) interlayers and compared to the Ohmic characteristics to Ti/ Au. [36] For the AZO process, the Ga 2 O 3 was implanted with Si, followed by a 10/20/80 nm thick AZO/Ti/Au stack. The AZO contact exhibited nearly linear I-V characteristics even as-deposited.…”
Section: Prospective Articlementioning
confidence: 99%
“…One is to form an intermediate semiconductor layer (ISL) with low work function by annealing, e.g., Ti 2 O 3 . The other is to insert the deposited ISL between the metal and β-Ga 2 O 3 , which has been intensively studied [7678]. Compared with the former method, the latter is more favorable to form Ohmic contacts owing to the high carrier concentration of ISL.…”
Section: Approaches To Ohmic Contactsmentioning
confidence: 99%
“…Lately, AZO/Ti/Au was used as electrodes on Si + -implanted β-Ga 2 O 3 , and the obtained specific contact resistivity was 2.82 × 10 −5  Ω∙cm 2 after annealing [76]. Oshima et al achieved platinum/indium–tin oxide (Pt/ITO) Ohmic contacts to β-Ga 2 O 3 with a wide range of process temperature window [77].…”
Section: Approaches To Ohmic Contactsmentioning
confidence: 99%
“…One potential method for reducing the contact resistance is to include a lower gap transparent conducting oxide as an interlayer between the metal and the wide bandgap semiconductor [22][23][24][25][26][27]. The most commonly used TCOs are indium tin oxide (ITO) and aluminum zinc oxide (AZO).…”
mentioning
confidence: 99%